1999
DOI: 10.1017/s1355617799511028
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning in cocaine abusers with and without alcohol dependence

Abstract: Thirty codependent cocaine and alcohol users were compared with age-, education-, race-, and sex-matched cocaine abusers (N 5 30) and normals (N 5 30) using an extended Halstead-Reitan Neuropsychological Test Battery to determine whether cocaine abusers with alcohol dependence were more cognitively impaired than singly addicted cocaine abusers. Tests were grouped and analyzed according to 8 major ability areas. Participants who abused both cocaine and alcohol did not differ from normals on the majority of test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
39
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 52 publications
10
39
2
2
Order By: Relevance
“…This would, nevertheless, be consistent with their status as "recreational users". There were no group differences in ethnicity, recoded into White versus non-White due to small case numbers [χ 2 (3)= 0.36, P=0.94], consistent with other studies (Robinson et al 1999;Di Sclafani et al 2002). It was not possible to analyze for differences in menstrual cycle phase between the two female groups due to small case numbers (and thus this variable will not be examined in further analyses).…”
Section: Participant Characteristicssupporting
confidence: 70%
See 2 more Smart Citations
“…This would, nevertheless, be consistent with their status as "recreational users". There were no group differences in ethnicity, recoded into White versus non-White due to small case numbers [χ 2 (3)= 0.36, P=0.94], consistent with other studies (Robinson et al 1999;Di Sclafani et al 2002). It was not possible to analyze for differences in menstrual cycle phase between the two female groups due to small case numbers (and thus this variable will not be examined in further analyses).…”
Section: Participant Characteristicssupporting
confidence: 70%
“…In addition, all participants were strictly excluded if they reported (1) any history of neurological or psychiatric illness in either self or first-degree relatives, (2) any history of alcohol or other substance abuse (except "cocaine use" in the cocaine user group, nicotine, and caffeine), (3) any alcohol consumption or other illicit drug use (other than "cocaine use" in the user group) during the prior 72 h, (4) any history of head injury or loss of consciousness, and (5) were not righthanded. These criteria are similar to those used in previous studies (Hoff et al 1996;Robinson et al 1999).…”
Section: Participantsmentioning
confidence: 77%
See 1 more Smart Citation
“…Many studies have demonstrated that drug dependence has a number of features in common with alcohol dependence, including symptomatology (Glatt, 1967;Heil et al, 2001), neuropsychological impairments (Robinson et al, 1999), pathogenetic mechanisms (Anokhina et al, 1990;O'Neill et al, 2001), and response to specific treatments, especially the effects of disulfiram, an ALDH blocker, which though approved for the treatment of alcohol dependence, has also been shown to be efficacious in the treatment of cocaine dependence (Carroll et al, 1993(Carroll et al, , 1998(Carroll et al, , 2004George et al, 2000;Petrakis et al, 2000). Drug dependence may share susceptibility genes with alcohol dependence (reviewed by Kreek et al, 2004), for example, OPRM1 gene variation moderated susceptibility to alcohol dependence and/or drug dependence (Hoehe et al, 2000;Szeto et al, 2001;Schinka et al, 2002;Luo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies have compared abstinent cocaine abusers to matched controls with or without a history of other substance use disorders (6). Several of these studies have documented poorer performance in abstinent cocaine users on measures of elemental cognitive functions including attention, vigilance, reaction time, psychomotor speed, and spatial and verbal memory (1,3,(6)(7)(8)(10)(11)(12)(13)(14)(15). In abstinent cocaine users, greater residual neurocognitive impairment is correlated with greater duration, frequency, peak dose and total amount of cocaine consumed per unit time (1 -3).…”
Section: Introductionmentioning
confidence: 99%